Implementation of Academic Supervision to Improve Teachers' Pedagogical Competence in Implementing Deep Learning (Multi Site Study: at SMK Tunas Bangsa and SMK Taman Bangsa) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to describe the implementation of academic supervision in enhancing teachers’ pedagogical competence in the practice of deep learning. The research employed a multi-site study with a qualitative descriptive approach, involving various stakeholders related to the implementation of academic supervision in schools, including school supervisors, principals, vice principals, quality assurance teams, human resource development teams, and teachers. Data were collected through observations, interviews, and document analysis. The validity of the data was tested using source triangulation, while the data analysis followed the Miles and Huberman (1994) framework, which consists of three stages: (1) data reduction, (2) data display, and (3) conclusion drawing. The findings reveal that the implementation of academic supervision at SMK Tunas Bangsa and SMK Taman Bangsa has been systematically, holistically, effectively, and sustainably planned, executed, and followed up. This implementation has had a positive impact on improving teachers’ pedagogical competence, particularly in applying deep learning.